Frequency of obesity and related risk factors among school children and adolescents in a low-income community: a cross-sectional study - Lima, Mariana Carvalheiro Cotrim; Romaldini, Ceres Concilio; Romaldini, João Hamilton (São Paulo Medical Journal, 2015)
CONTEXT AND OBJECTIVE: The frequency of obesity at an early age may contribute to atherosclerosis and cardiovascular disease (CVD) in adults. This study measured the frequency of obesity and cardiovascular risk factors in children and adolescents aged 6 to 17 years. DESIGN AND SETTING: Cross-sectional study in a school located in a region of low income and socioeconomic status in Santa Rita do Sapucai, Minas Gerais, Brazil. METHODS: A total of 175 students were classified using body mass index (BMI) and their waist circumference, blood pressure, number of hours of sedentary behavior and school meals were evaluated. Serum concentrations of fasting blood glucose, total cholesterol (TC), triglycerides (TG), low-density lipoprotein (LDL-C) and high-density lipoprotein (HDL-C) were analyzed. RESULTS: 37.2% of the students had BMI above the 85th percentile and had significantly lower age, higher prevalence of hypertension, higher serum TC, LDL-C and TG, and greater waist circumference than those with BMI below the 85th percentile. Hypertension was observed in 2.9% of the students; 5.1% presented impaired glucose tolerance, 40% had two risk factors for atherosclerosis and 26.9% had three risk factors. A sedentary lifestyle was significantly less prevalent among subjects with BMI above the 85th percentile and was significantly correlated with serum TC and LDL-C. The school meals were hypoglycemic, hyperproteic and hyperlipidemic. CONCLUSION: One third of the children and adolescents had weights greater than or equal to the age-adjusted weight, and this was associated with greater waist circumference, hypertension and prevalence of dyslipidemia.